(untitled) (Asian Journal of Medical and Biological Research, 2021)
Functional independence is an integral part for reflection of quality of living. Many scales have been utilised for it and the Barthel Index (BI) is one of them, which later modified on 10 activities having the score range of 0-20. English version of the Modified Barthel Index (MBI) is widely used to measure disability also in Bangladesh and an important tool for assessment of activities of daily living in aged patients. However, a validated and culturally adapted Bengali version of MBI has not been produced yet. This study describes the validation and reliability into Bengali of the modified 10-item version of MBI, and reports the procedures for testing its validity and reliability. For validation process a two phased study was conducted based on data from aged patients in out and in patient department of Bangabandhu Sheikh Mujib Medical University. After pre-testing of the Bengali version of MBI (B-MBI) among 30 aged patients in phase-1 of the study whereas total 129 patients were submitted to the adapted scale for testing its acceptability and internal consistency in second phase. The internal consistency by Cronbach’s alpha resulted equal to 0.880. The score was also tested against the Bengali adapted SF-36 (Short Form-36) to compare with physical functioning and mental health domains. It yielded Spearman’s correlation coefficient (rS) 0.787 (p<0.001)), indicating strong positive correlation of B-MBI with physical functioning part and a weak correlation (rs=0.191; p=0.031) was found with mental health domain of SF-36. Reliability was evaluated on 124 cases as 5 participants were missed for re-test; at test-retest was ICC=0.961 (95%IC: p<0.001). This study provides a new tool for professionals in Bangladesh to measure functional disability in aged patients both in inpatient and outpatient department of hospitals and also in the health and social care settings along the continuum of care. Asian J. Med. Biol. Res. 2021, 7 (3), 238-248